ANDRAGOGICAL MODEL OF THE FORMATION OF PROFESSIONAL COMPETENCE AMONG STUDENTS OF A VOCATIONAL EDUCATIONAL INSTITUTION - M. D. Kurbanova (Galaxy International Interdisciplinary Research Journal, 2021)
The article reveals the essence of the basic concepts of the formation of professional competence in students on the basis of the andragogical approach, the peculiarities of the process of the formation of professional competence. The importance of professional competence of a specialist in the modern labor market is recognized. The article also proposes the author’s technology for the formation of professional competence of students based on the androgynous approach.